Biodiversity in Locally Managed Lands - Jeffrey Sayer (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This volume assembles papers that provide empirical evidence for the success or otherwise of landscape and community or local government managed initiatives to conserve biodiversity. The papers report successful biodiversity conservation projects that have operated at those scales as well as documenting cases where these approaches were attempted but were less successful. The papers identify the conditions under which these local and landscape approaches have succeeded and those under which they have been less successful.